2020
DOI: 10.1111/jam.14548
|View full text |Cite
|
Sign up to set email alerts
|

Identification of antimicrobial metabolites produced by a potential biocontrol Actinomycete strain A217

Abstract: Aims To extract and identify the metabolites of strain A217 as well as its antifungal spectrum and control effect on various plant pathogens. Methods and Results Strain A217 was identified as a Streptomyces sp. which was most similar to Streptomyces lienomycini. An antimicrobial spectrum test indicated that strain A217 inhibited several plant pathogenic fungi and strong antibacterial effect such as Phytophthora capsici, Botrytis cinerea, Sclerotinia sclerotiorum, Fusarium oxysporum, Pseudomonas syringae and Xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
(39 reference statements)
0
17
0
1
Order By: Relevance
“…Eleven pathogenic bacteria were used in this study, five of which were significantly inhibited in in vitro and in vivo assays ( Figure 7 ), including X. campestris pv. jugiandis (cause of black rot in walnut) [ 40 ]), E. carotovora subsp. carotovora (cause of soft rot in potatoes and vegetables) [ 41 , 42 ]), and P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven pathogenic bacteria were used in this study, five of which were significantly inhibited in in vitro and in vivo assays ( Figure 7 ), including X. campestris pv. jugiandis (cause of black rot in walnut) [ 40 ]), E. carotovora subsp. carotovora (cause of soft rot in potatoes and vegetables) [ 41 , 42 ]), and P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid generation of ROS is called an oxidative burst and provides extremely harsh environments for pathogens. He et al studied the mechanism of α-lycopene on fungal cell death induced by filamentous pathogenic fungus F. oxysporum and found that α-lycopene causes ROS outbreak and depolarization of mitochondrial membrane potential in F. oxysporum (He et al 2020).…”
Section: Fs-4 Can Induce Oxidative Stress and Apoptosis In Foc4mentioning
confidence: 99%
“…2015), cellulose (Singh and Gaur 2016), nuclease (He et al . 2020) and so on. The cell wall of pathogenic bacteria is used for their own growth by breaking down nutrients that cause the death of pathogenic bacteria (Wang et al .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Estudos demonstraram o potencial das actinobactérias como agentes de controle biológico de fitopatógenos em culturas de interesse econômico (SOLTANZADEH et al, 2016;GOMES et al, 2018;HAO et al, 2020). As actinobactérias, particularmente o gênero Streptomyces, são reconhecidas pelo seu potencial em produzir uma vasta quantidade de metabólitos secundários, dentre os quais se destacam as substâncias antibióticas (ANZAI et al, 2008;BARRETO et al, 2008;DURAIPANDIYAN et al, 2010;MIYAUCHI, 2012).…”
Section: Introductionunclassified